Asupan Karbohidrat dan Aktifitas Fisik pada Siswa SMP dengan Status Gizi Gemuk di Kota Tasikmalaya - Listianasari, Yanita; Putra, Ahmad Faris Eka (JGK: Jurnal Gizi dan Kesehatan, 2023)
Background: Overweight and obesity are conditions of excess carbohydrates and fat in adipose tissue and pose a risk of damaging health. The prevalence of obesity aged 13 – 15 years is 8,3% and obesity is 2,5%. Objective: This research is to determine carbohydrate intake and physical activity in junior high school students who experience overweight and obesity nutritional status in Tasikmalaya City. Method: This research is a descriptive study with a cross sectional design which was carried out from February to April 2023. Data were collected using anthropometric measurements to determine the nutritional status of respondents, interviews using the SQ-FFQ and IPAQ formulas to determine carbohydrate intake and physical activity. Data collections used a total sampling technique of 20 respondents. Results: There were 20 respondents who were obese. Most respondents were aged 13 – 14 years (85%). The majority of gender is male at 90%. Respondents with obesity were 50% and non-obese were 50%. Carbohydrate intake in the over category is 35%. Light physical activity is 20%, moderate physical activity is 75%. Conclusion: Overweight and obese teenagers at junior high school/ equivalent level experience problems with excessive carbohydrate intake and light or moderate physical activity.